Activation of AMPK in platelets promotes the production of offspring - Tong Zhang; Mengnan Yang; Shujun Li; Rong Yan; Kesheng Dai (Platelets)
Platelets are terminally differentiated anucleated cells, but they still have cell-like functions and can even produce progeny platelets. However, the mechanism of platelet sprouting has not been elucidated so far. Here, we show that when platelet-rich plasma(PRP) was cultured at 37°C, platelets showed a spore phenomenon. The number of platelets increased when given a specific shear force. It is found that AMP-related signaling pathways, such as PKA and AMPK are activated in platelets in the spore state. Meanwhile, the mRNA expression levels of genes, such as CNN3, CAPZB, DBNL, KRT19, and ESPN related to PLS1 skeleton proteins also changed. Moreover, when we use the AMPK activator AICAR(AI) to treat washed platelets, cultured platelets can still appear spore phenomenon. We further demonstrate that washed platelets treated with Forskolin, an activator of PKA, not only platelet sprouting after culture but also the AMPK is activated. Taken together, these data demonstrate that AMPK plays a key role in the process of platelet budding and proliferation, suggesting a novel strategy to solve the problem of clinical platelet shortage.